Altered amphiregulin expression induced by diverse luteinizing hormone receptor reactivity in granulosa cells affects IVF outcomes. Issue 6 (June 2015) - Huang, Ying; Zhao, Yue; Yu, Yang; Li, Rong; Lin, Shengli; Zhang, Chunmei; Liu, Ping; Qiao, Jie
Abstract The expression of specific genes (LHR, AREG, EREG, EGFR, NPPC and NPR2) involved in peri-ovulatory signalling pathways induced by LH surge in granulosa cells was investigated, and their relationships with IVF outcomes analysed. mRNA levels of the genes of 147 infertile women undergoing IVF and intracytoplasmic sperm injection (ICSI) with embryo transfer were evaluated. Compared with non-pregnant women, amphiregulin (AREG) mRNA levels in mural and cumulus graunulosa cells were significantly higher (P < 0.05) in pregnant women, and were positively correlated with number of oocytes retrieved and good-quality embryos. No significant differences were found between the two groups in the remaining detected genes. To investigate the reason for the differences in AREG expression, mural granulosa cells were cultured and stimulated with human chorionic gonadotrophin (HCG) for 2–24 h. At 4 h after HCG stimulation, AREG and epiregulin mRNA expression peaked, with much greater increases in the pregnant group. The fold-change of AREG expression was positively correlated with number of good-quality embryos. No obvious correlation, however, was found between NPPC/Npr2 expression levels in granulosa cells and IVF outcomes. Altered AREG expression induced by diverse luteinizing hormone receptor reactivity in granulosa cells may provide a useful marker for oocyte developmental competency.